Черняхівські поховання могильника Дідів Шпиль на Канівщині - Терпиловський, Р.В.; Петраускас, О.В. (Археологія, 2005)
До наукового обігу вводяться матеріали ранньогунського періоду з могильника Дідів Шпиль на Дніпрі, відомого насамперед як пам'ятка зарубинецької культури. Кремації та тілопокладення зі слідами ритуального руйнування належали черняхівській общині, що включала різні етнокультурні компоненти. В 1971—1975 гг. Каневской экспедицией во главе с Е.В. Максимовым был исследован могильник Дедов Шпиль на берегу Днепра между сс. Бучак и Бобрица Каневского р-на Черкасской обл. На площади 3600 кв. м выявлено 52 погребения, большая часть которых принадлежала зарубинецкой культуре. Вместе с тем представляют интерес также четыре погребения (три кремации и трупоположение), сопровождающий инвентарь которых позволяет отнести их к финалу позднеримского времени. С этим же периодом можно, очевидно, связать еще более десятка безынвентарных погребений, преимущественно трупоположений со следами ритуального разрушения, обычного для черняховской культуры. Необычная топография, отсутствие в погребениях гончарной керамики ставят могильник на особое место в черняховской культуре. По двум гребням типа III, по Томас, и подвязной фибуле рассматриваемые комплексы датируются ранним гуннским временем. В погребальной обрядности сочетаются восточногерманские (готские), а также славянские и сарматские черты, что говорит о синкретическом характере оставившей могильник общины. In 1971—1975 Kaniv expedition headed by E.V. Maksimov explored the Didiv Shpyl burial ground on the bank of the Dnieper River between the villages Buchak and Bobritsa of the Kaniv Region in Cherkassy Oblast’. Fifty-two burials were discovered over the area of 3600 sq. m., some of which were found to belong to Zarubinets culture. Four more burials (three cremations and one inhumation) deserve attention as we 11. By the grave goods discovered there the burials are attributed to the very end of the Roman period. Evidently a dozen more burials can be associated with the same period. They are mostly inhumation ones, without any grave goods, but with traces of ritual destruction common for Chemyakhi v culture. Unusual topography and absence of pottery in the burials distinguish this burial ground from others belonging to Chemyakhiv culture. In accordance with two combs of Type III by Tomas and a tying-up fibula the assemblages in discussion can be dated back to the Early Huns period. The burial rites combine East German (Gothian), as well as Slavonic and Sannatian features thus speaking in favor of syncretic character of the community which had left the burial ground.